Identification and isolation of endothelial cells based on their increased uptake of acetylated-low density lipoprotein. - John C. Voyta; D P Via; Catherine Butterfield; Bruce R. Zetter (1984)
Acetylated-low density lipoprotein (Ac-LDL) is taken up by macrophages and endothelial cells via the "scavenger cell pathway" of LDL metabolism. In this report, aortic and microvascular endothelial cells internalized and degraded 7-15 times more [125I]-Ac-LDL than did smooth muscle cells or pericytes. Bound [125I]-Ac-LDL was displaced by unlabeled Ac-LDL, but not unmodified LDL. The ability to identify endothelial cells based on their increased metabolism of Ac-LDL was examined using Ac-LDL labeled with the fluorescent probe 1,1'-dioctadecyl-3,3,3',3'-tetramethyl-indocarbocyanine perchlorate (Dil-Ac-LDL). When cells were incubated with 10 micrograms/ml Dil-Ac-LDL for 4 h at 37 degrees C and subsequently examined by fluorescence microscopy, capillary and aortic endothelial cells were brilliantly fluorescent whereas the fluorescent intensity of retinal pericytes and smooth muscle cells was only slightly above background levels. Dil-Ac-LDL at the concentration used for labeling cells had no effect on endothelial cell growth rate. When primary cultures of bovine adrenal capillary cells were labeled with 10 micrograms/ml of Dil-Ac-LDL for 4 h at 37 degrees C, then trypsinized and subjected to fluorescence-activated cell sorting, pure cultures of capillary endothelial cells could be obtained. Utilizing this method, large numbers of early passage microvascular endothelial cells can be obtained in significantly less time than with conventional methods.